Development of an Edu-Tourism Module Based on QR-Code Flora Diversity in Villa Tani Indonesia to Support Students’ Flora Identification Skills - Tahri Tahri; Pipit Marianingsih; Dwi Ratnasari (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
Technology always develops to be adapted to human needs. One type of technology is educational technology, which is used as a special tool to facilitate the education and learning process, such as QR-Code. This research aimed to develop teaching tools in the form of edu-tour modules by utilizing QR-Code technology to support students’ flora identification skills. The study used the research and development (R&D) method, with the research design referring to the 3D model (Define, Design, & Develop). The research was conducted in May 2023 – May 2024 at Villa Tani Indonesia, SMAN 5 Kota Serang, and Sultan Ageng Tirtayasa University. The feasibility test based on media experts showed a value of 97.22% with a very good category, while based on material experts showed a value of 87.18% with a very good category. The student response test from class X students of SMAN 5 Kota Serang and visitors to Villa Tani Indonesia obtained a score of 88.08% in the very feasible category.